P209 Rates of wound healing in patients with Crohn's disease undergoing proctectomy. (25th January 2019) - Grant, R; Bouri, S; Elosua González, A; Dilke, S; Sahnan, K; Adegbola, S; Warusavitarne, J; Tozer, P; Hart, A
Abstract: Background: The purpose of this study was to determine factors which may be associated with poor wound healing in patients with perianal Crohn's disease (pCD) who had undergone proctectomy in the biologics era. Methods: Case record review was carried out of 79 patients with pCD who underwent proctectomy at St Mark's Hospital, Harrow between 2005 and 2017. Healing rates at 6 and 12 months post proctectomy were considered and univariate regression analysis was performed. Results: Complete data regarding healing were available for 97.5% (77/79) at 6 months and 100% at 12 months. 45/77 (43.7%) patients had failure of wound healing at 6 months and 34/79 (33%) at 12 months. A younger age at diagnosis of Crohn's disease was significantly associated with failure of healing at 12 months (median age 21 ± 9.7 unhealed; median age 27 ± 13.6 healed; p = 0.03). 76.7% (61/79) patients received biologic treatments prior to proctectomy; however, exposure to biologics was not a significant factor in predicting failure of wound healing (Infliximab p = 0.74; Adalimumab p = 0.57; Vedolizumab p = 0.21). Current smoking status was not associated with poor wound healing ( p = 0.18). Other parameters which were not associated with failure of wound healing in our cohort included gender, corticosteroid exposure in the previous 1 month, thiopurine exposure in previous 3 months, number of biologics exposed to, perianal sepsis on MRI within the last 12 months, Montreal Classification, duration of Crohn's disease prior to proctectomy, albumin, and CRP. Conclusions: A third of patients have unhealed wounds after 1-year follow-up after protectomy. A younger age at diagnosis of Crohn's disease was the only factor associated with an unhealed perineal wound. This is conducive with more severe disease progression witnessed in patients diagnosed at a younger age. Larger scale studies are required to more accurately determine if other parameters such as exposure to biologics may also play a role in predicting rates of wound healing.